EVALUASI KUALITAS INFORMASI APBDES DALAM LAPORAN REALISASI ANGGARAN SERTA DAMPAKNYA TERHADAP TATA KELOLA KEUANGAN DESA - Awalia, Cici; Hambali, Denny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to evaluate the information Anggaran Pendapatan dan Belanja Desa (APBDes) within the laporan Realisasi Anggaran (LRA) in Seteluk Atas Village, West Sumbawa Regency, and analyze its influence on strengthening village financial management. By applying a qualitative descriptive approach, this study examines data through observation, documentation, and in-depth interviews with village officials, such as the Village Head, Village Secretary, and Treasurer. The research indicates that Seteluk Atas Village has produced high-quality financial information, as evidenced by the alignment between budget realization reaching 97.7% of the target and the utilization of the SISKEUDES application in accordance with Permendagri Number 20 of 2018. Public transparency is clearly reflected through the publication of APBDes infographic billboards that facilitate participatory oversight by the community. Theoretically, these activities reflect the application of Stewardship Theory, where village officials function as managers who prioritize integrity and the community's interests over personal interests. In conclusion, accurate and transparent information in Seteluk Atas Village not only fulfills administrative responsibilities but also serves as a solid foundation for realizing accountable village governance (good village governance).